Analyzing form-based zoning's potential to stimulate mixed-use development in different economic environments. (February 2017) - Hughen, W. Keener; Read, Dustin C.
Abstract: Form-based zoning ordinances can provide real estate developers with the ability to alter the mix of residential and commercial space included in their projects so long as they comply with design requirements governing the exterior of buildings. The real option model presented in this paper quantifies the value of this flexibility to assess the potential impact on development decisions and developer profits across market settings. The results suggest form-based zoning may stimulate development in weak markets with volatile demand. However, it may not consistently encourage a greater mixing of real estate product types in comparison to other land use regulations.